2020
DOI: 10.1186/s12987-020-00216-1
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of microvascular pathology in the neurological manifestations of coronavirus infection

Abstract: Human coronaviruses are highly pathogenic viruses that pose a serious threat to human health. Examples include the severe acute respiratory syndrome outbreak of 2003 (SARS-CoV-1), the Middle East Respiratory Syndrome (MERS-CoV) outbreak of 2012, and the current SARS-CoV-2 (COVID-19) pandemic. Herein, we review the neurological manifestations of coronaviruses and discuss the potential pathogenic role of blood–brain barrier dysfunction. We present the hypothesis that pre-existing vascular damage (due to aging, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 101 publications
(228 reference statements)
0
24
0
Order By: Relevance
“…Moreover it was recently described that the virus can directly infect neurons and can be found in the brain or in the CSF of COVID-19 patients (15)(16)(17)(18). In addition, numerous pathologies affecting neurovasculature have been reported in patients, such as thromboembolism or ischemic stroke, highlighting a potential role of the BBB in the neurological COVID-19 diseases (60,61). Despite these observations, the mechanisms of SARS-CoV-2 access to the brain are poorly described.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover it was recently described that the virus can directly infect neurons and can be found in the brain or in the CSF of COVID-19 patients (15)(16)(17)(18). In addition, numerous pathologies affecting neurovasculature have been reported in patients, such as thromboembolism or ischemic stroke, highlighting a potential role of the BBB in the neurological COVID-19 diseases (60,61). Despite these observations, the mechanisms of SARS-CoV-2 access to the brain are poorly described.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that SARS-CoV-2 may directly affect cells of the NVU and lead to neurological dysfunction [87]. In vitro, Buzhdygan et al [88] found that the spike protein of SARS-CoV-2 induced a loss of brain endothelial cell barrier integrity and triggered a proinflammatory response.…”
Section: Sars-cov-2/ Covid-19mentioning
confidence: 99%
“…Many factors, including frailty, comorbidities (e.g., hypertension, diabetes, cardiovascular disease, and chronic respiratory disease), and compromised immune function may contribute to worse health outcomes and a high mortality rate. Cardiovascular disease, diabetes, hypertension, or other comorbidities, preexisting microvascular pathology may further facilitate the neuroinvasion of the coronavirus and contribute to the development of neuropsychiatric symptoms and neuropathology associated with the viral infection [ 5 ]. The presence of chronic neurological comorbidity is an independent predictor of all-cause mortality in hospitalized COVID-19 patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%